Gap analysis of maternity service quality and associated factors at a maternity hospital in northwest Iran: a cross-sectional survey using SERVQUAL and HEALTHQUAL questionnaires - Parnian Rahimi; Farzaneh Miri; Alireza Hajizadeh; Azadeh Anbari; Jafar Sadegh Tabrizi; Edris Kakemam (BMC Pregnancy and Childbirth)
Abstract Background Concerning maternity service, the mother’s quality assessment is central because emotional, cultural, and respectful support is vital during labour and the delivery process. Studies concerning the perceived quality of maternity services from the perspective of mothers have rarely been carried out in Iranian hospital settings. Therefore, this study aimed to measure the gap between the expectations of patients with maternity services and their perceptions of the service and identify associated factors at a maternity hospital in northwest Iran using service quality (SERVQUAL) and health quality (HEALTHQUAL) questionnaires. Methods This cross-sectional study consists of 350 randomly selected participants visiting a maternity hospital in Tabriz, Iran between November 2022 and February 2023. Admitted patients responded to two questionnaires adopted from the SERVQUAL and HEALTHQUAL instruments. The questionnaire was provided on hospital admission for expectation and before hospital discharge for perception. The quality gaps between the expectations and perceptions of participants were analyzed. Data were analyzed using SPSS (Version 24) through descriptive analyses, paired t-tests, and multivariate linear regression. Results Based on the SERVQUAL questionnaire, the overall score for expectation and perception were 3.69 and 4.15, respectively and the overall gap in service quality was − 0.45. Similarly, according to the HEALTHQUAL questionnaire, the overall score for expectation and perception were 3.66 and 4.53, respectively, and the overall gap in service quality was − 0.87. In addition, the results indicated that the highest gap was observed for the Effectiveness and Assurance dimensions with gap scores of − 1.20 and − 0.69, respectively. Older patients, having an academic education, women who were residents in urban and those who visited for the first time were found to have significantly higher expectations compared with their perceived quality of care (P < 0.005). Conclusions The results of the current study confirmed that there is a negative gap between maternity service women’s expectations and their perceptions. These results suggest there is capacity for improvement in the quality of health service delivery from the patient’s perspective. Therefore, hospital managers need to develop several strategies to improve the interpersonal skills of staff and communication, strengthen trust between patients and health providers, and meet the psychological and emotional needs of patients.